On the reduction of constants in plane elasticity with eigenstrains (Archives of Mechanics - Test, 2002)
In this paper the reduced parameter dependence in linear plane elasticity with eigenstrains (transformation strains) is studied. The focus is on simply connected inhomogeneous materials and two-phase materials with perfectly bonded interfaces. In the analysis we rely on the result of Cherkaev, Lurie and Milton (Proc. Roy. Soc. Lond. A 438, 519-529, 1992), and we show that the stress field is invariant under a shift in area bulk and shear compliances, if the eigenstrains obey certain conditions. The analysis can be extended to multiply connected inhomogeneous materials and materials with slipping interfaces.